Enhanced photoresponse and high photo-detectivity in chemically deposited MoS2 thin films with inherent strain. (December 2021) - Dam, Siddhartha; Thakur, Abhishek; Hussain, Shamima
Abstract: Photoresponse of thin film heterojunctions of MoS2 /Si synthesised by chemical bath deposition technique have been studied. Presence of strain as confirmed by Raman and XRD was found to be the cause of this enhancement. Particle size calculated from FESEM was found to increase with annealing temperature. XPS studies were used to ascertain the phases precisely. The valence band maxima was found to decrease with the increase in the inherent of strain. A very high photo-detectivity (~10 13 ) was found for the samples having 24% of MoS3 .